2016
DOI: 10.1111/jam.13041
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with the clay mineral palygorskite affects performance and beneficially modulates caecal microbiota in laying pullets

Abstract: The novelty of this study lies to the beneficial effect of palygorskite (a clay mineral) to pullets growth and health, likely through modulation of the gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
2
19
0
1
Order By: Relevance
“…But Zhang, Yan, Zhang, Wen, and Zhou () found that 5 g/kg palygorskite inclusion in pellet diet could improve ADG and ADFI of broilers, whereas did not affect F:G. Otherwise, it has been proved that 2,000 mg/kg Pal inclusion could significantly decrease the F:G of weaned piglets (Zhang et al., ), which is consistent with the current study. Similar result can also be observed in laying hens (Chalvatzi, Kalamaki, Arsenos, & Fortomaris, ). The positive effect of MPal on the growth performance of broilers in this study might result in the proper additive amount and feed form.…”
Section: Discussionsupporting
confidence: 85%
“…But Zhang, Yan, Zhang, Wen, and Zhou () found that 5 g/kg palygorskite inclusion in pellet diet could improve ADG and ADFI of broilers, whereas did not affect F:G. Otherwise, it has been proved that 2,000 mg/kg Pal inclusion could significantly decrease the F:G of weaned piglets (Zhang et al., ), which is consistent with the current study. Similar result can also be observed in laying hens (Chalvatzi, Kalamaki, Arsenos, & Fortomaris, ). The positive effect of MPal on the growth performance of broilers in this study might result in the proper additive amount and feed form.…”
Section: Discussionsupporting
confidence: 85%
“…Both diets increased the abundance of OTU 1, which is an anaerobic bacterium that ferments carbohydrates to lactic acid. Olsenella spp., has been identified in the GIT of laying pullets being involved in lipid and cholesterol metabolism [25]. On the other hand, the observed increase of L. crispatus (OTU 3) could be considered desirable, because this phylotype has been classified as a beneficial probiotic, in poultry [26].…”
Section: Resultsmentioning
confidence: 99%
“…We speculate this might be related to the positive effect of clay mineral on the establishment of favourable bacteria in the intestine, as described by Chalvatzi et al ., who showed that a more favourable microbiota was found in clay mineral supplemented groups in comparison with control groups in a 18‐week study on laying pullets (Chalvatzi et al . ).…”
Section: Discussionmentioning
confidence: 97%